Reporting of data monitoring committees and adverse events in paediatric trials: a descriptive analysis - Allison Gates; Patrina Caldwell; Sarah Curtis; Leonila Dans; Ricardo M Fernandes; Lisa Hartling; Lauren E Kelly; Katrina Williams; Kerry Woolfall; Michele P Dyson; Ben Vandermeer (BMJ Publishing Group, 2019)
Objectives For 300 paediatric trials, we evaluated the reporting of: a data monitoring committee (DMC); interim analyses, stopping rules and early stopping; and adverse events and harm-related endpoints.Methods For this cross-sectional evaluation, we randomly selected 300 paediatric trials published in 2012 from the Cochrane Central Register of Controlled Trials. We collected data on the reporting of a DMC; interim analyses, stopping rules and early stopping; and adverse events and harm-related endpoints. We reported the findings descriptively and stratified by trial characteristics.Results Eighty-five (28%) of the trials investigated drugs, and 18% (n=55/300) reported a DMC. The reporting of a DMC was more common among multicentre than single centre trials (n=41/132, 31% vs n=14/139, 10%, p<0.001) and industry-sponsored trials compared with those sponsored by other sources (n=16/50, 32% vs n=39/250, 16%, p=0.009). Trials that reported a DMC enrolled more participants than those that did not (median [range]): 224 (10-60480) vs 91 (10-9528) (p<0.001). Only 25% of these trials reported interim analyses, and 42% reported stopping rules. Less than half (n=143/300, 48%) of trials reported on adverse events, and 72% (n=215/300) reported on harm-related endpoints. Trials that reported a DMC compared with those that did not were more likely to report adverse events (n=43/55, 78% vs 100/245, 41%, p<0.001) and harm-related endpoints (n=52/55, 95% vs. 163/245, 67%, p<0.001). Only 32% of drug trials reported a DMC; 18% and 19% did not report on adverse events or harm-related endpoints, respectively.Conclusions The reporting of a DMC was infrequent, even among drug trials. Few trials reported stopping rules or interim analyses. Reporting of adverse events and harm-related endpoints was suboptimal.